If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying u(6u + -7) = 0 Reorder the terms: u(-7 + 6u) = 0 (-7 * u + 6u * u) = 0 (-7u + 6u2) = 0 Solving -7u + 6u2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), 'u'. u(-7 + 6u) = 0Subproblem 1
Set the factor 'u' equal to zero and attempt to solve: Simplifying u = 0 Solving u = 0 Move all terms containing u to the left, all other terms to the right. Simplifying u = 0Subproblem 2
Set the factor '(-7 + 6u)' equal to zero and attempt to solve: Simplifying -7 + 6u = 0 Solving -7 + 6u = 0 Move all terms containing u to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6u = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 6u = 0 + 7 6u = 0 + 7 Combine like terms: 0 + 7 = 7 6u = 7 Divide each side by '6'. u = 1.166666667 Simplifying u = 1.166666667Solution
u = {0, 1.166666667}
| 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 | | 6w+5w-9w=12 | | 5y(y+2)=0 | | 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 | | (3g+2)(9g+5)=0 | | 5(10)-2=38 | | 300+12=960 | | 6-(x+9)=3-4x | | 10x-7y=-42 | | (d-6)(d-2)=0 | | 3(8)+7=25 | | 8(x+1)+3=7x+18 | | 3x-5(x+2)=12x+4 | | (v-7)(v-6)=0 | | 0.27t=129 | | 3+x=43 | | 96c^2+336c+294=0 | | 2(3)-5=17 | | v^2=-14+9v |